2011
DOI: 10.1097/aap.0b013e318228d5d4
|View full text |Cite
|
Sign up to set email alerts
|

Is Sciatic Nerve Block Advantageous When Combined With Femoral Nerve Block for Postoperative Analgesia Following Total Knee Arthroplasty?

Abstract: Sciatic nerve block (SNB) is commonly performed in combination with femoral nerve block (FNB) for postoperative analgesia following total knee arthroplasty (TKA). This systematic review examines the effects of adding SNB to FNB for TKA compared with FNB alone on acute pain and related outcomes. Four intermediate-quality randomized and 3 observational trials, including a total of 391 patients, were identified. Three of 4 trials investigating the addition of single-shot SNB and 2 of 3 trials investigating contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 30 publications
1
36
0
2
Order By: Relevance
“…The present quantitative review nonetheless points to level 1a-(minus) evidence 42 (i.e., representing a systematic review with significant heterogeneity) in support of the SNB, a notable improvement from the level 2a-evidence supporting SNB that we observed in our earlier qualitative review of the literature. 14 Our results also suggest that SSNB can reduce pain at rest and during movement up to eight hours postoperatively, whereas CSNB can reduce pain at rest up to 36 hr and pain with movement up to 48 hr. The relative superior analgesia associated with CSNB compared with SSNB during the first eight hours postoperatively may well be attributable to the extensive multi-modal analgesic regimen used in CSNB trials.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The present quantitative review nonetheless points to level 1a-(minus) evidence 42 (i.e., representing a systematic review with significant heterogeneity) in support of the SNB, a notable improvement from the level 2a-evidence supporting SNB that we observed in our earlier qualitative review of the literature. 14 Our results also suggest that SSNB can reduce pain at rest and during movement up to eight hours postoperatively, whereas CSNB can reduce pain at rest up to 36 hr and pain with movement up to 48 hr. The relative superior analgesia associated with CSNB compared with SSNB during the first eight hours postoperatively may well be attributable to the extensive multi-modal analgesic regimen used in CSNB trials.…”
Section: Discussionsupporting
confidence: 59%
“…[11][12][13] Unfortunately, the relevant evidence examining the role of SNB had been limited to observational studies and lowquality randomized controlled trials (RCTs), thus precluding a valid and reliable estimation of effect. 14 Recently, however, nine RCTs have been separately published, with seemingly mixed results. [15][16][17][18][19][20][21][22][23] In this updated meta-analysis, we aimed to quantify the analgesic effects of adding proximal single-shot or continuous SNB to single-shot or continuous FNB in the absence of LIA on analgesic consumption and pain scores during the first 48 hr postoperatively in adult patients undergoing unilateral TKA.…”
mentioning
confidence: 99%
“…Other similar studies found opposing results: Carli et al [8] found no differences in pain scores and Toftdahl et al [34] and Affas et al [2] found lower scores in patients receiving periarticular injection compared with those receiving isolated femoral nerve blocks during the first postoperative day [2,8,34]. The use of combined sciatic and femoral nerve blocks over femoral nerve block alone has been shown to have improved pain scores and seems more beneficial for pain management [1,10,17]. When comparing intraoperative periarticular injections with intraarticular injections given after closure of the capsule, better pain scores are generally found in studies using periarticular injections [12,15,30,36].…”
Section: Discussionmentioning
confidence: 98%
“…Many authors have shown that periarticular injections provide improved pain relief compared with no injection [6,22,36]. Additionally, numerous studies have compared the efficacy of various types of neuraxial anesthetics and peripheral blocks [1,7,23,28,31,37,38]. The addition of a sciatic block to a femoral block provides better pain relief than femoral block alone, and various combinations have been studied [4,7,10,17,37].…”
Section: Introductionmentioning
confidence: 99%
“…There are many meta-analysis studies were supporting that adding SNB to FNB can reduce postoperative opioid consumption and decreased the postoperative pain VAS score in the first 24 h after TKR [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%